1997
DOI: 10.1046/j.1365-2141.1997.d01-2075.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA analysis for evidence of apoptosis in megaloblastic anaemia

Abstract: Summary. This study involved DNA analysis of bone marrow cells of 15 patients with megaloblastic anaemia. The diagnosis was based on the morphological changes seen in the bone marrow, associated with either a low red cell folate or serum vitamin B12 level and an adequate response to appropriate therapy as confirmation of the diagnosis. Flow cytometric DNA analysis showed an increase in the S and G 2 phases of the cell cycle, but conventional agarose gel electrophoretic DNA analysis did not confirm the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Lymphocyte apoptosis can be prevented by vitamin B 12 administration and may thus improve immunologic abnormalities observed in pernicious anemia. Previous studies suggested that ineffective hematopoiesis caused by vitamin B 12 deficiency concerned primarily CD8+ cells [11,12] . In our patients with pernicious anemia, decline in absolute numbers of lymphocytes and CD8+ cells was partially restored by vitamin B 12 administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphocyte apoptosis can be prevented by vitamin B 12 administration and may thus improve immunologic abnormalities observed in pernicious anemia. Previous studies suggested that ineffective hematopoiesis caused by vitamin B 12 deficiency concerned primarily CD8+ cells [11,12] . In our patients with pernicious anemia, decline in absolute numbers of lymphocytes and CD8+ cells was partially restored by vitamin B 12 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 12 deficiency results in megaloblastic anemia, peripheral nervous system disorder, and in animal models, depression of immune defense against viruses and bacteria [8] . It has been reported that vitamin B 12 treatment restores the immune parameters in patients with megaloblastic anemia [1][2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring or synthetic inhibitors of histone deacetylases can cause cell cycle ar- rest, differentiation and apoptosis in neoplastic cells opening a door to explore newer cancer chemotherapy strategies [34,35] . It is possible that changes in nuclear histones coupled with altered chromatin may also impair regulation of cell cycle checkpoints promoting apoptosis in megaloblastic bone marrows as suggested by several recent studies [36][37][38][39] . Recently, it has been reported that the nuclear histone content of bone marrows in lower mammalian species such as rats is much higher than that of higher mammalian species such as rhesus monkey [40] .…”
mentioning
confidence: 99%
“…When folate defi ciency was induced in monkeys, their bone marrow developed fl orid megaloblastic transformation, and this was associated with marked reduction of particularly arginine-rich histones, but folate-defi cient rats did not develop megaloblastic transformation, although DNA synthesis was impaired as indicated by abnormal dU suppression values. This can be explained by the initially high histone content in the bone marrow cells in the rats, which was not suffi ciently reduced even in established folate defi ciency to reach a critically low level required for megaloblastic transformation [36] . A postulated scheme of molecular events in the development of megaloblastosis is given in fi gure 9 .…”
mentioning
confidence: 99%